Peran Green Human Resources Management Sebagai Pemediasi Hubungan Green Transformational Leadership dan Green Servant Leadership Terhadap Green Creativity Pada Jasa Hotel dan Pariwisata - Siswadhi, Ferry; Widyastuti, Tri; Sawitri, Ni Nyoman; Munir, Ningky Sasanti; Ali, Hapzi; Lestari, Anggia Ayu (Universitas Pahlawan Tuanku Tambusai, 2024)
The study aims to investigate the impact of e-service quality and e-returns service quality on e-customer loyalty in the Hotel in Kerinci and Sungai Penuh. It is a quantitative study. Purposive sampling was used with a questionnaire distributed to 80 hotel employees. Results indicate hhat Green Transformational Leadership and Green Servant Leadership directly influence Green Human Resources Management on Green Creativity. Green Human Resources Management and Green Creativity, strengthening the exchange relationship between employees and the organization by valuing their contributions. When green practices and changes benefit the hotel, employees will work harder and enjoy eco-friendly tasks. Encourage employees` environmental creativity.